Mineralogical and geochemical characterization of the Old Tailings Dam, Australia: Evaluating the effectiveness of a water cover for long-term AMD control. (May 2016) - Jackson, Laura M.; Parbhakar-Fox, Anita
Abstract: Establishing a shallow water cover over tailings deposited in a designated storage facility is one option to limit oxygen diffusion and retard oxidation of sulfides which have the potential to form acid mine drainage (AMD). The Old Tailings Dam (OTD) located at the Savage River mine, western Tasmania contains 38 million tonnes of pyritic tailings deposited from 1967 to 1982, and is actively generating AMD. The OTD was constructed on a natural gradient, resulting in sub-aerial exposure of the southern area, with the northern area under a natural water cover. This physical contrast allowed for the examination of tailings mineralogy and geochemistry as a function of water cover depth across the OTD. Tailings samples (n = 144, depth: ≤ 1.5 m) were collected and subjected to a range of geochemical and mineralogical evaluations. Tailings from the southern and northern extents of the OTD showed similar AMD potential based on geochemical (NAG pH range: 2.1 to 4.2) and bulk mineralogical parameters, particularly at depth. However, sulfide alteration index (SAI) assessments highlighted the microscale contrast in oxidation. In the sub-aerial zone pyrite grains are moderately oxidized to a depth of 0.3 m (maximum SAI of 6/10), under both gravel fill and oxidized covers, with secondary minerals (e.g., ferrihydrite and goethite) developed along rims and fractures. Beneath this, mildly oxidized pyrite is seen in fresh tailings (SAI = 2.9/10 to 5.8/10). In the sub-aqueous zone, the degree of pyrite oxidation demonstrates a direct relationship with cover depth, with unoxidized, potentially reactive tailings identified from 2.5 m, directly beneath an organic-rich sediment layer (SAI = 0 to 1/10). These findings are broadly similar to other tailings storage facilities e.g., Fox Lake, Sherritt-Gordon ZnCu mine, Canada and Stekenjokk mine, Sweden where water covers up to 2 m have successfully reduced AMD. Whilst geotechnical properties of the OTD restrict the extension of the water cover, pyrite is enriched in cobalt (up to 2.6 wt%) indicating reprocessing of tailings as an alternative management option. Through adoption of an integrated mineralogical and geochemical characterization approach for tailings assessment robust management strategies after mine closure can be developed. Graphical abstract: Highlights: Legacy sulfide-rich mine tailings in western Tasmania generating AMD. Contrast in tailings deposition, with sub-aerial and sub-aqueous zones. Variation in tailings oxidation highlighted by sulfide alteration index. Sulfide oxidation limited by a water cover of 0.87–2.5 m depth. Reprocessing tailings to extract cobalt a future management option.